Neuro-imaging in severe hypertensive disorders of pregnancy: a study from North Indian tertiary health care institution - Dogra, Rohit; Thakur, Rama; Thakur, Vijay; Pal, Anita; Chamotra, Shaina; Chaudhary, Ankit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorders of pregnancy comprising of pre-eclampsia and eclampsia are a major cause of adverse pregnancy outcomes. Neurological manifestations of pregnancy induced hypertension are the most common cause of maternal and foetal morbidity and mortality. Cranial neuro-imaging reveals focal regions of symmetric hemispheric oedema; with parietal and occipital regions getting most commonly affected. Methods: The study was conducted among 65 antenatal women diagnosed with pre-eclampsia and eclampsia at gestational age >20 weeks in the department of obstetrics and gynecology, Kamla Nehru State Hospital for Mother and Child IGMC Shimla. Clinical signs and symptoms, neuroimaging findings were recorded for study purpose. Results: About 17.6% of severe pre-eclampsia and 100% of eclampsia had findings observed on cranial MRI. Headache and visual complaints were most frequently recorded. PRES was the predominant neuroradiographic finding in present study and occipital lobe was commonly affected region. No significant difference was observed regarding blood pressure parameters between MRI positive and negative subjects. Conclusions: Neuroimaging in antenatal with severe hypertensive disorders might aid in better understanding of the poorly explained phenomenon. In addition, this would be helpful in better management of the disorders along with their much-dreaded complications. Patients with hypertensive disorders of pregnancy should be subjected routinely to cranial imaging for the better perinatal outcomes.